Algebra I

Thanks Reiny, but I'm still lost. I understand how you multipled by 10X on the right to get 17x, but you went too fast on the left, and I have no idea how you got 10x^2-20 from the starting left side. Can you show each step?
Thanks,
Carol

x - 2(1/x) = 17/10

multiply each term by 10x

10x^2 - 20 = 17x
10x^2 - 17x - 20 = 0
(5x + 4)(2x - 5) = 0

so x = -4/5 or x = 5/2

check:
reciprocal of 5/2 is 2/5
twice the reciprocal is 4/5
evaluate 5/2 - 4/5
= (25-8)/10 = 17/10

  1. 👍 0
  2. 👎 0
  3. 👁 97
asked by Carol
  1. x * 10x = 10x^2

    2/x * 10x = 20 (The x's cancel each other out.)

    Thus 10x(x -2/x) = !0x^2 - 20

    I hope this helps a little more. Thanks for asking.

    1. 👍 0
    2. 👎 0
    posted by PsyDAG

Respond to this Question

First Name

Your Response

Similar Questions

  1. Intermediate Algebra

    Determine whether the point (1, 8) is a solution of the system 2x + 6y = 50 10x + 0y = 10 by substituting the point into each equation. So far I have: 2x=6y=50 y=50-2x 10x+10y=10 10x+0(50-2x)=10 10x+0=10 x=10 y=50-2x y=50-2(1)

    asked by Jordan on October 7, 2010
  2. Math - Alg

    How much pure acid must be added to a 30% acid solution to make a 60L solution which is 50% acid? This was the answer I got from Reiny. amount of pure acid to be added -- x L 1(x) + .3(60-x) = .5(60) 10x + 3(60-x) = 5(60) 10x +

    asked by Brittany Jones on February 8, 2014
  3. Algebra Help! Please

    Ok so I did what you told me reiny but I cant figure out number three which is here 10x - 2 - 6x = 3x - 2 + x Please show how You did it please?

    asked by Jeff on November 19, 2014
  4. math

    Posted by connie on Monday, July 20, 2009 at 11:56pm. Find the indicated outputs for f(x) = 2x²-4x f(0)= ____? f(-1) =____? f(2) =____? Responses math - Reiny, Tuesday, July 21, 2009 at 8:00am f(0) = 2(0)^2 - 4(0) = 0*0 = 0 f(-1)

    asked by connie on July 21, 2009
  5. Pre-algebra

    Solve. 29x – 2(9x – 0.455) = 10x + 0.525 Give us you thinking on this so we can help you solve the equation. What is it you don't understand about solving this eqution? 29x –2(9x – 0.455) = 10x + 0.525 29x – 18x – 0.91

    asked by Tammy Evert on July 16, 2006
  6. how about his one

    -7+ 5x = 10x-2? im not sure I know its -1, but im not sure how. -7 + 5x = 10x - 2 Since we need to get the unknowns on one side and the knowns on the other side and change their signs: 5x - 10x = 7 - 2 -5x = 5 x = -1 wait how did

    asked by chrissy on August 1, 2007
  7. Geometry

    Line MP bisects

    asked by Steven on September 10, 2016
  8. Math

    Find the equation of the tangent line 5x^2+y^2=14 at (1,3). P.S: It's calculus. So far I know this much 10x+2y(dy/dx)=o -10x -10x ___________________ 2y(dy/dx)= -10x (dy/dx)= -10x/2y= -5x/y m= -5(1)/3= -5/3 y=mx+b 3= -5/3(1)+b

    asked by Skye on February 7, 2008
  9. Math Algebra 1

    i was wondering if anyone could help me on this problem. expand: x^-2 (y^2 + 10x) z^3 (5x + 3z^-4) First one: x^-2 (y^2 + 10x) x^-2 is the same thing as 1/x^2. Therefore, we have this: 1/x^2 (y^2 + 10x) Multiply using the

    asked by cassii on August 8, 2006
  10. Algebra 2

    "My husband's age," remarked a lady the other day, "is represented by the figures of my own age reversed. He is my senior, and the difference between our ages is one-eleventh of their sum." 10x + y = husband's age 10y + x = wife's

    asked by Anonymous on October 25, 2011

More Similar Questions